Motivasi Berprestasi Baca Tulis Al-Qur’an pada Penyandang Tunanetra di Pimpinan Daerah Ikatan Tunanetra Muslim Indonesia di Palembang - Haliya Haliya; Eko Oktapiya Hadinata (Fakultas Psikologi, Universitas Islam Negeri Raden Fatah Palembang, 2021)
This study aims to find out how the description of achievement motivation for blind people in the regional leadership of the Indonesian Muslim blind association in Palembang. The research sample was three members of the regional leadership of the Indonesian Muslim blind association in the city of Palembang and the factors that influence the achievement motivation of reading and writing the Qur'an in Indonesian Muslim blind people in the regional leader of the Indonesian Muslim blind association in Palembang. This research uses descriptive qualitative research. Based on the research findings and discussion, it can be concluded that students with visual impairments have similarities in learning methods, namely still using braille, the three subjects, although disabled, have motivation in achieving various achievements in the field of reading and writing the Al-Qur'an nationally and internationally.